تمويل الحملة الانتخابية في ضل قانون الانتخابات الجديد 2021 - بحري, مريم (جامعة الوادي.University eloued, 2021)
"تهدف دراستنا التي تتمحور حول الحملة الانتخابية في ظل القانون الجديد إلى انه من خلال تعدد المترشحين في الانتخابات يشتد التنافس بينهم، فكل مرشح يحاول أن يبرز نفسه بالإعلان عن برنامجه ومقترحاته السياسية وفق ما يقتضيه القانون وكذلك ما يعرف بالحملة الانتخابية ولكي لا تعم الفوضى وضع المشرع الجزائري مجموعة من القوانين لتنظيمها من توقيت ومدة الحملات الانتخابية وكما تهدف هذه الدراسة إلى تسويق الحملات الانتخابية مع تحديد عوامل نجاح الانتخابات والتي يجب أن تكون مسلمة ونزيهة وإلا كنا امام منازعات في القائمة الانتخابية. وفي الاخير توصلنا إلى أن الحملة الانتخابية تتم وفق استراتيجيات واساليب محددة وفي مدة معينة وفي ظل ما يقتضيه القانون الانتخابي.""Our study, which revolves around the election campaign under the new law, aims to that through the multiplicity of candidates in the elections is highly competitive among them, each candidate tries to highlight himself by announcing his program and political proposals as required by law as well as what is known as the election campaign and in order not to be chaotic the Algerian legislator put a set of laws to organize them from the timing and duration of election campaigns and as this study aims to market campaigns while identifying the factors of electoral success which must be Muslim and fair otherwise we would be facing disputes on the electoral list. In the end, we have concluded that the election campaign is conducted in accordance with specific strategies and methods, in a certain period and under the requirements of the electoral law."
قانون إداري
Keywords: الحملة الانتخابية ، القانون الانتخابي، المشرع الجزائري ،الانتخابات; The electoral campaign, the electoral law, the Algerian legislator, the elections